2002
DOI: 10.1136/heart.87.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine induced PR jump on surface ECG to differentiate atrioventricular nodal re-entrant tachycardia from concealed accessory pathway mediated tachycardia: a bedside test

Abstract: Objective: To evaluate the efficacy of single dose intravenous adenosine in differentiating atrioventricular nodal re-entrant tachycardia (AVNRT) from concealed pathway mediated atrioventricular re-entrant tachycardia (AVRT) using surface ECG at the bedside. Method: 12 mg of adenosine was administered to 97 consecutive patients who had documented narrow QRS tachycardia without manifest pre-excitation. The test was labelled positive for AVNRT if surface ECG recordings showed signs of dual atrioventricular (AV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Adenosine administration can unmask pathway conduction in patients with latent preexcitation and demonstrate dual AV nodal conduction in some patients with AVNRT [4] with a sensitivity of 74%, but is cumbersome to perform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenosine administration can unmask pathway conduction in patients with latent preexcitation and demonstrate dual AV nodal conduction in some patients with AVNRT [4] with a sensitivity of 74%, but is cumbersome to perform.…”
Section: Discussionmentioning
confidence: 99%
“…History of neck pulsation, age at onset of symptoms and female sex have been shown to indicate the diagnosis of AVNRT [1][2][3]. Administration of adenosine or adenosine tri-phosphate has also been used to unmask accessory pathway conduction or dual atrioventricular nodal physiology [4][5][6]. Studies using venography have shown that the coronary sinus (CS) is larger and has a wind--sock shape in patients with AVNRT compared to controls [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Side effects, such as sinus pauses and bradycardia following termination of the arrhythmia, were directly correlated with the dose employed. Other investigators focused their interest on the pharmacological effects of the very short-acting drug adenosine [7,8,13] . Burkart et al [13] used a mean dose of 7.1 8 3.9 mg adenosine to block the AV node while pacing the atrium.…”
Section: Discussionmentioning
confidence: 99%
“…Only those patients who demonstrated neither a significant PR jump nor a high-grade AV block after injection of 12 mg adenosine received an 18-mg bolus of adenosine intravenously after a waiting period of another 5 min. Furthermore, the occurrence of AV nodal echo beats or AV reentrant echo beats was evaluated based on the definition of previous studies [4,5,8] . The results were reviewed and graded by two independent electrophysiologists.…”
Section: Adenosine Testmentioning
confidence: 99%
See 1 more Smart Citation